Magic lost, trouble found - Shearin, Lisa (New York : Ace Books, 2007)
A new fantasy series launches with this title. Raine Benares is a Sorceress Seeker of average ability until she comes into possession of an amulet that amplifies her powers--and her enemies. Original.
Keywords: Magic; Thieves; Amulets; Fantasy fiction